Mobile Application Design for Startup Zyon Using Design Thinking Method - Ajeng Yunita; Budi Praptono; Tiara Verita Yastica (International Journal of Innovation in Enterprise System, 2023)
Zyon is one of the startups in the mental health field that concern of inadequate handling of mentalhealth issues. Consequently, the design of the Zyon application is driven by the aim of addressingthese challenges and providing user-oriented solutions. This research focuses on the integration ofusers and psychologists on a platform, using the design process that incorporates the five stages ofdesign thinking: empathize, define, ideate, prototype, and test. Through in-depth interviews,observations, and expert validation, a conceptual framework for the Zyon application wasformulated, resulting in the creation of application mockups. The Zyon application offersconsultation services and a range of features to enhance the interaction between users andpsychologists, ultimately aligning with user needs. The application design, validated byrespondents using the System Usability Scale (SUS) with a score of 87.75, signifies its highusability and fulfillment of acceptable requirements. This research contributes to the advancementof mental health services by delivering an effective and user-friendly application that caters to theneeds of its users and psychologists.